ANALISIS KESULITAN MAHASISWA DALAM MENGERJAKAN SOAL ELIPS - Yuwono, Muhammad Ridlo; Firmansah, Fery; Syaifuddin, M. Wahid (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
This study aims to analyze students' difficulties in working on ellipse problems. Descriptive research with a qualitative approach is the type of this research. Students of the Mathematics Education Study Program at Widya Dharma University, Klaten who are taking the analytical geometry course were selected as the subjects of this study. This study places the role of the researcher as the main instrument and the ellipse test and interview guidelines as supporting instruments. The triangulation method technique by comparing the results of the ellipse test with interviews is used to obtain valid data on the difficulties experienced by students in working on ellipse problems. The three stages of data analysis in this study include data condensation, data presentation, and drawing conclusions. The results of this study are that students' difficulties in working on ellipse problems include difficulty in conveying reasons for the answers given based on a geometric review and forgetting the formula for lateral recta.